PENGARUH PENDIDIKAN GIZI MELALUI PERMAINAN ULAR TANGGA TERHADAP PENGETAHUAN GIZI REMAJA - Anugrah, Riva Mustika; Wening, Dyah Kartika; Anisya, Yolan Fatkhis (UNIVERSITAS NGUDI WALUYO, 2018)
Background: One of caused of nutritional problems in adolescents are poor nutritional knowledge. Balanced Nutrition Guidelines for adolescents need to be delivered with interesting media to easy understood and applied in daily life. The snakeladder media with students as a piece is expected to improve nutrition knowledge in adolescents. Objective: it aimed the effect of snakes and ladders on nutritional knowledge of adolescent Method :This study included experimental research with one grouppre-post design, the selection of subjects with stratified random sampling and obtained 186 students of SMAN 2 Ungaran dan SMAN 2 Tuntang in class X and XII students. Assessment of nutritional status of students with BMI/U. Knowledge measurement with questionnaires before and after snakes and ladders. The effect of the snake ladder game on students' nutritional knowledge was tested using paired t-test. Results: The average knowledge of nutrition of students before the intervention was 75.78±8.95 and increased to 90.37±6.3. There is an increase in nutrition knowledge of adolescents after playing snakes and ladders (p <0.005). Conclusion :Nutrition education with snack ladder improve knowledge of student Abstrak : Latar Belakang : Penyebab terjadinya masalah gizi pada remaja salah satunya adalah kurangnya pengetahuan gizi. Pedoman Gizi seimbang pada remaja perlu disampaikan dengan sebuah media yang menarik supaya mudah dipahami dan di aplikasikan dalam kehidupan sehari hari. Media ular tangga dengan siswa sebagai bidaknya diharapkan dapat meningkatkan pengetahuan gizi pada remaja. Tujuan : mengetahui pengaruh permainan ular tangga terhadap pengetahuan gizi remaja Metode : Penelitian ini termasuk penelitian eksperimental dengan one group pre-post design, pemilihan subjek dengan stratified random sampling dan didapatkan 186 siswa SMA Negeri 2 Ungaran dan SMA Negeri 2 Tuntang pada siswa kelas X dan XII. Penilaian status gizi siswadengan IMT/U. Pengukuran pengetahuan dengan kuesioner sebelum dan sesudah permainan ular tangga. Pengaruh permainan ular tangga terhadap pengetahuan gizi siswa diuji dengan menggunakan paired t-test. Hasil: Rata-rata pengetahuan gizi siswa sebelum intervensi yaitu 75,78±8,95 dan meningkat menjadi 90,37±6,3. Terdapat peningkatan pengetahuan gizi remaja setelah melakukan permainan ular tangga ( p<0,005). Simpulan : Permainan ular tangga meningkatkan pengetahuan gizi pada remaja